2009
DOI: 10.1075/jpcl.24.2.03heb
|View full text |Cite
|
Sign up to set email alerts
|

Scrabble as a tool for Haitian Creole literacy

Abstract: This paper argues that Scrabble can be used as a tool to help maintain and grow all levels of Haitian Creole literacy and it provides the technical details for developing the game. The rules of the English version are given to introduce the game’s basic structure. Haiti’s educational, sociolinguistic, and literacy conditions are presented in order to put in context the orthographic form proposed for the Haitian Creole version. An overview of game culture in Haiti shows Scrabble’s potential for success. Previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…For Haitian Creole historical linguistics see Hebblethwaite (2001). For writing on literacy and Haitian Creole games see Hebblethwaite (2009a). For research on Haitian Creole genesis see Lefebvre (1998).…”
Section: The Sociolinguistic Situation Of Haitian-americans In South mentioning
confidence: 99%
“…For Haitian Creole historical linguistics see Hebblethwaite (2001). For writing on literacy and Haitian Creole games see Hebblethwaite (2009a). For research on Haitian Creole genesis see Lefebvre (1998).…”
Section: The Sociolinguistic Situation Of Haitian-americans In South mentioning
confidence: 99%
“…While conducting additional Haitian Creole Scrabble fieldwork in Haiti in 2010, 2 I realized that digraphs or trigraphs on single tiles amount to a design defect that leads to underperformance in game play. Contrary to Pierre Paul (cited in Juste 2005) and Hebblethwaite (2009), I now argue that Haitian Creole Scrabble is most playable when each tile receives one and only one letter on it. Testing showed time and again that a phonemic approach that assigns digraphs and trigraphs like ch, ou, an, en, on, tch or ui to single letter tiles significantly limits the expansion of the collectively built cross-word on the Scrabble game board by making the arrangement of words too compact.…”
mentioning
confidence: 59%
“…REJCAP currently has a website where the group promotes Haitian Creole Scrabble through workshops and seeks donations to expand their effort to promote the game in Haiti. REJCAP's version of Scrabble, like Hebblethwaite (2009), promotes the use of digraphs on single tiles. However, I have found that a version of the game in which each tile receives one and only one letter performs far better in game play.…”
mentioning
confidence: 99%
“…This study focuses on three key research questions related to the impact of these learning media on students' mastery of discourse markers and overall speaking abilities. The findings reveal that despite the potential of Scrabble and flashcards to enhance speaking skills-a fact supported by several studies (Hebblethwaite, 2009;Ramdhani, 2022;Utami et al, 2021)-many students still struggle with basic English vocabulary. This struggle is often due to educational practices overemphasizing grammar and using traditional methods like dictionary-based learning, which may not effectively address vocabulary and discourse marker mastery needs.…”
Section: Figure 1 Interactive Effects Of Variablesmentioning
confidence: 73%